DEVELOPMENT AND VALIDATION OF HEALTH EDUCATIONAL MATERIAL ON ANAEMIA PREVENTION IN PREGNANCY IN EKITI STATE, NIGERIA - Abiodun-Ojo, Olubukola; Bello, Cecilia; Ogundipe, Laofe; Adebayo, Ebunoluwa (African Journal of Research in Medical and Health Sciences, 2025)
Background: Anaemia in pregnancy is a major cause of feto-maternal mortality and morbidity, and pregnant women require necessary information through health education using educative material for its prevention. This study aimed to develop and validate flipchart on anaemia prevention among pregnant women in Ekiti State. Methods: Multistage sampling technique was used to select 6 Comprehensive Health Centres (CHC) from selected LGAs, and an exploratory sequential mixed method was utilized for the study. The flipchart was developed based on eight (8) expert panel consensus and validated using the Content Validity Index (CVI). Sample size was calculated using Cochrane formular. The Qualitative data were analysed thematically based on themes explored from the focus group discussions. The Quantitative phase was analysed using McNemars test (a good tool for testing effectiveness). Results: The integrated findings demonstrated that although pregnant women's awareness of anaemia in pregnancy was adequate, their knowledge of causes and prevention was inadequate. The newly developed flipchart on anaemia prevention was unanimously rated as valid with an S-CVI of 0.96 to 1.00 and S-CVI/UA of 0.75 to 1.00 by experts. The developed flipchart for appropriateness was evaluated favourably based on its contents, how well the pictures depicted feto-maternal consequences, and the primary messages it conveyed. There were significant differences in the effectiveness of the two educational methods for both control and intervention groups for pregnant women, using the McNemars test (post-test odd ratio = 7.458, pre-test odd ratio = 1.963, p =. 000 <. 05). McNemar p-value of 0.000 was significant at less than 0.05 significant level. Conclusion: Conclusively, the developed flipchart is a valuable tool for health education and can be used to support patients' wellness.